Aboveground Biomass and Carbon Stocks of an Undisturbed Regenerating Sal (Shorea Robusta Gaertn. F.) Forest Of Goalpara District, Assam, Northeast India - Rabha, Debajit (International Journal of Environment, 2014)
The present paper deals with the above ground biomass and carbon stocks of an undisturbed Sal forest of Goalpara district, Assam, Northeast India. The average AGB and C were recorded 239.45 ± 12.8 Mg ha-1 and 119.73 ± 6.4 Mg ha-1. Density distribution curve indicates the high carbon sequestration potential of the stand in near future which further helps in climate change mitigation. Currently, conservation measures are well imposed in combine effort of local community and government. Legal involvement of local community in conservation exercises along with the forest department might be very effective in management of Sal forests. DOI: http://dx.doi.org/10.3126/ije.v3i4.11743 International Journal of Environment Volume-3, Issue-4, Sep-Nov 2014 Page: 147-155